2008
DOI: 10.1002/pd.2163
|View full text |Cite
|
Sign up to set email alerts
|

PLAC4 and β‐HCG mRNA levels are not altered in the maternal circulation of pregnancies with trisomy 21

Abstract: Maternal blood levels of beta-HCG-, PLAC4- and PAPP-A mRNAs are not useful markers for the screening of pregnancies with trisomy 21 as their concentrations are either not significantly altered (beta-HCG and PLAC4) or too low to be detected (PAPP-A).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
3
5
0
Order By: Relevance
“…The discoveries of cell-free fetal DNA [4] and later placental mRNA [5] in maternal plasma have offered new opportunities for the development of noninvasive prenatal diagnosis [9]. More recently, placental expressed and pregnancy-associated transcripts have been reported to be detectable in maternal whole blood [10][14]. As the RNA yield in whole blood far exceeds that of plasma, we explored in this study if maternal whole blood might represent a better specimen type for the detection of fetal specific placenta-derived mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The discoveries of cell-free fetal DNA [4] and later placental mRNA [5] in maternal plasma have offered new opportunities for the development of noninvasive prenatal diagnosis [9]. More recently, placental expressed and pregnancy-associated transcripts have been reported to be detectable in maternal whole blood [10][14]. As the RNA yield in whole blood far exceeds that of plasma, we explored in this study if maternal whole blood might represent a better specimen type for the detection of fetal specific placenta-derived mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…CSH1 , CGB and placenta-specific 4 ( PLAC4 , NM_182832) mRNA concentrations were reported to be much higher in maternal whole blood than plasma [12], [14]. Indeed, the total RNA content of whole blood is higher than plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the chromosome 21 identified candidate genes, PLAC-4 was the most abundant and was later shown to be polymorphic. Furthermore, it has recently been shown that the expression of PLAC-4 is unaltered in trisomy 21 fetuses [26].…”
Section: Determination Of Fetal Aneuploidy By Allelic Ratio Discriminmentioning
confidence: 99%
“…It has been further proposed that the SNPs associated with such candidate genes need to be different between mother and father in order to achieve allelic discrimination [16,37]. However, one group showed that the expression of PLAC4 is unaltered in trisomy 21 fetuses [72].…”
Section: Determination Of Fetal Aneuploidy By Allelic Ratio Discriminmentioning
confidence: 99%